A Four-Step Technique for Creating Individual Double-Eyelid Crease Shapes: A Free-Style Design. Issue 4 (October 2020) - Suo, Linlang; Li, Jiaqi; Fu, Rao; Xie, Yun; Huang, Ru-Lin
Abstract : Background: Double-eyelid blepharoplasty is the most frequently performed aesthetic surgery in the Asian population. However, the epicanthal fold has been a conundrum limiting the outcomes of Asian blepharoplasty. Furthermore, with the blending of Western and Asian cultures, patients have individual standards of beauty for the upper eyelids. Here, we developed a four-step technique to form infold or outfold double-eyelid creases to satisfy individual patient requirements. Methods: The medical records of patients who simultaneously underwent double-eyelid blepharoplasty and epicanthoplasty using this four-step technique from January of 2017 to January of 2019 were reviewed. The results were grouped by preoperative patient requirements for eyelid crease shapes. The rate of meeting patient expectations in each group was evaluated by two independent observers. Preoperative and postoperative photographs were collected, complications were identified, and postoperative results were assessed. Results: In total, 285 consecutive patients were included in this study, with a mean follow-up period of 9 months. Of the 285 patients, 207 requested infold eyelid creases, and 190 (92 percent) procedures met patient expectations; and 78 patients requested outfold eyelid creases, and 69 (87 percent) procedures met patient expectations. A high rate of satisfaction with the final eyelid crease shape and resulting scarring was noted in both patient groups. The revision rate was 3 percent. No severe complications were observed. Conclusion: The four-step technique is a simple, flexible, and effective method for creating infold or outfold double-eyelid creases according to individual patient requirements and should be considered a routine method for patients who request double eyelids. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, IV. Abstract : Supplemental Digital Content is available in the text.